Pengelolaan Sumberdaya Ikan Bada (Rasbora sp) di Danau Maninjau, Sumatra Barat - Gita Natalia Taruk Linggi (Program Studi Manajemen Sumber Daya Perairan, 2020)
Bada fish is one of the high economic value fish resources that live in Lake Maninjau. Overfishing of bada fish by fishermen without paying attention to aspects of fish biology can lead to population decline. This study aims to analyze the form of bada fish management by looking at its biological aspects. This research was conducted at the Limnology Research Center of the Indonesian Institute of Sciences (LIPI) Cibinong, Bogor in May-December 2019. Bada fish samples were collected from Lake Maninjau using fishing gear nets, lukah and chart. For the purposes of the analysis, the length and weight of the bada fish were measured and the level of maturity of the gonads. In this study, the t-test (partial) was carried out as an analysis of the parameters of the relationship between length and weight of fish. The results of this study indicate the growth of bada fish in Lake Maninjau based on the results of measurements of length and weight, namely length 21 mm - 124 mm with a weight of 0.01 gr - 13.85 g. The equation of the long relationship weight of female bada fish W = 3.1247L5,4128 , male bada fish W = 3.1296L5,4283 and combined W = 3.163L5,4899. The male dan female bada fish growth pattern is a positive allometric growth pattern. The value of the condition factor was obtained in female and male bada fish, namely 1.3086 and 1.0176. The highest results of bada fishing TKG III and IV were obtained in November. Therefore, it is concluded that the form of management can be carried out by limiting the size of the mesh, prohibiting the operation of non-selective fishing gear, modifying fishing gear, and regulating the catching season.